2017
DOI: 10.1186/s13045-017-0390-6
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-2 promotes prostate cancer bone metastasis by the up-regulation of matrix metalloproteinase-2 through down-regulating miR-376c expression

Abstract: BackgroundThrombospondin-2 (TSP-2) is a secreted matricellular glycoprotein that is found to mediate cell-to-extracellular matrix attachment and participates in many physiological and pathological processes. The expression profile of TSP-2 on tumors is controversial, and it up-regulates in some cancers, whereas it down-regulates in others, suggesting that the functional role of TSP-2 on tumors is still uncertain.MethodsThe expression of TSP-2 on prostate cancer progression was determined in the tissue array by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 47 publications
2
58
0
Order By: Relevance
“…Notably, the rs1045411 polymorphism resides in the 3ʹ-flanking region and may therefore affect HMGB1 gene expression. Previous studies have also indicated that the rs1045411 polymorphism reduces the risk of oral squamous cell carcinoma and gastric cancer development 31 , 32 . Findings from the GTEx database in the current study confirm that variant T at rs1045411 shows a reduced trend in HMGB1 expression, compared with the wild-type C homozygous genotypes.…”
Section: Discussionmentioning
confidence: 96%
“…Notably, the rs1045411 polymorphism resides in the 3ʹ-flanking region and may therefore affect HMGB1 gene expression. Previous studies have also indicated that the rs1045411 polymorphism reduces the risk of oral squamous cell carcinoma and gastric cancer development 31 , 32 . Findings from the GTEx database in the current study confirm that variant T at rs1045411 shows a reduced trend in HMGB1 expression, compared with the wild-type C homozygous genotypes.…”
Section: Discussionmentioning
confidence: 96%
“…Extranuclear signaling has been linked to rapid responses to E2 via stimulation of mitogen-activated protein kinase (MAPK), especially p38MAPK, protein kinase B (AKT), phosphatidylinositol-3-kinase (PI3K) in the cytosol [ 18 , 19 ]. Mechanistically, considering the fact that a key biological function of MAPK/AKT is regulation of the expression of MMPs [ 36 39 ], we found that MMP-2 activation induced by ERβ were significantly associated with p38MAPK and AKT phosphorylation in vitro and in vivo . Taken together, these results demonstrated that estrogen regulates MMP-2 expression via ERβ and may promote metastasis through the p38MAPK and PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…MMP2/9 forms complexes with THBS2 to interact with LRP1 and gets degraded; however, THBS2 could also regulate MMPs indirectly (26). The results from the present study demonstrated that CUX1 mediated the effect of THBS2 on MMP9.…”
Section: Discussionmentioning
confidence: 49%
“…Deregulation of THBS2 induces adhesion, apoptosis, migration and cytoskeletal organization of cancer cells (25). Chen et al (26) reported that THBS2 promoted prostate cancer bone metastasis by inducing miR-376c-mediated MMP2 upregulation. Cancer-associated fibroblasts also suppressed prostate cancer invasion via modulation of the ERα/THBS2/MMP3 axis (27).…”
Section: Discussionmentioning
confidence: 99%